SISTEM PENUNJANG KEPUTUSAN DIAGNOSIS PENYAKIT HIPERTENSI DENGAN METODE NAIVE BAYES CLASSIFIER - Randy Ramadhiansa (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Decision Support System is useful to make a decision. One example of  decision support system is Naive Bayes Classifier. The purpose of this application is to help the general public in diagnosis hypertension disease. So, public can also be quickly treat hypertension disease This method will help decision makers  make decisions only by requiring small amount of training data to determine parameter, Criteria used in the application are age, pulse, blood pressure (diastolic and systolic), height and weight. Evaluation and testing on this application using questionnaires. The questionnaires have been distributed to the user, and the results from testing these applications can be concluded is already fit for use to the public in early diagnosis of hypertension disease, that this application is suitable for use in the community to diagnosis hypertension.